Salinity Effects on Microbial Derived-C of Coastal Wetland Soils in the Yellow River Delta - Shao, Pengshuai; Han, Hongyan; Sun, Jingkuan; Yang, Hongjun; Xie, Hongtu (Frontiers in Ecology and Evolution, 2022)
Microorganisms play a crucial role in regulating the turnover and transformation of soil organic carbon (SOC), whereas microbial contribution to SOC formation and storage is still unclear in coastal wetlands. In this study, we collected topsoil (0–20 cm) with 7 salinity concentrations and explored the shifts in microbial residues [represented by amino sugar (AS)] and their contribution to the SOC pool of coastal wetlands in the Yellow River delta. The gradually increasing soil salinity reduced soil water content (SWC), SOC, and soil nitrogen (N), especially in high salinity soils of coastal wetlands. Total ASs and their ratio to SOC, respectively, decreased by 90.56 and 66.35% from low salinity to high salinity soils, indicating that coastal wetlands with high salinity restrained microbial residue accumulation and microbial residue-C retention in the SOC pool. Together with redundancy analysis and path analysis, we found that SWC, pH, SOC, soil N, and glucosamine/muramic arid were positively associated with the ratio of ASs to SOC. The higher available soil resource (i.e., water, C substrate, and nutrient) increased microbial residue accumulation, promoting microbial derived-C contribution to SOC in low salinity coastal wetlands. The greatly decreased microbial residue contribution to SOC might be ascribed to microbial stress strategy and low available C substrate in coastal wetlands with high salinity concentration. Additionally, the gradually increasing salinity reduced fungal residue contribution to SOC but did not change bacterial residue contribution to SOC. These findings indicated that changed fungal residues would substantially influence SOC storage. Our study elucidates microbial contribution to SOC pool through residue reservoir in coastal wetlands and pushes microbial metabolites to a new application in global wetland SOC cycling.